Global Virology II - HIV and NeuroAIDS - Shapshak, Paul; Levine, Andrew J.; Foley, Brian T.; Somboonwit, Charurut; Singer, Elyse (Springer, 2017)
This book on NeuroAIDS, a collection of chapters written by experts and specialists from around the world, provides a global perspective on HIV and NeuroAIDS in the field, clinic, and laboratory. The chapters address the comorbidity of HIV and other infectious agents, including Zika virus, Ebola, Chagas disease, TB and HCV. Also discussed are key topics, such as: Molecular socioepidemiology, Global HIV and NeuroAIDS, Neuropathology, cART and blood-brain barrier penetration, HIV replicative oscillations, HIV and SIV evolution, Psychiatric comorbidities, Neurosyphilis, The examination of current and innovative models of translational research to translational effectiveness.- Resumé vydavatel